Older people's use of ambulance services: a population based analysis. Issue 2 (1st March 1999) - Clark, M J; FitzGerald, G
Abstract : OBJECTIVE: To investigate the use of emergency and non-urgent ambulance transport services by people aged 65 years and over. SETTING: The study was undertaken in Queensland where the Queensland Ambulance Services (QAS) is the sole provider of emergency pre-hospital and non-urgent ambulance services for the entire state. METHODS: The age and sex of 351, 000 emergency and non-urgent cases treated and transported by the QAS from July 1995 to June 1996 were analysed. RESULTS: People aged 65 years and over who comprise 12% of the population utilise approximately one third of the emergency and two thirds of the non-urgent ambulance resources provided in Queensland. While the absolute number of occasions of service for females for emergency services is higher than for males, when the data are stratified for age and sex, males have higher rates of emergency ambulance service utilisation than females across every age group, and particularly in older age groups. Gender differences are also found for non-urgent ambulance usage. The absolute number of occasions of service for older females aged 65 and over using non-urgent ambulance transport is high, but utilisation patterns on stratified data reveal similar gender usage patterns across most age groupings, except at the older age groupings where male usage greatly exceeds female usage. CONCLUSIONS: As the aged are disproportionately high users of ambulance services, it will become increasingly important for ambulance services to plan for the projected increase in the aged population. Emergency pre-hospital care is one of the few health services along the continuum of care where male usage patterns are higher than those of females. More information needs to be obtained on the age and presenting characteristics of those people who are multiple users of the ambulance service. Such information will assist service planners.